Glucagon-like peptide-1 analogs against antipsychotic-induced weight gain: potential physiological benefits - Ebdrup, Bjørn H (BioMed Central, 2012)
BACKGROUND: Antipsychotic-induced weight gain constitutes a major unresolved clinical problem which may ultimately be associated with reducing life expectancy by 25 years. Overweight is associated with brain deterioration, cognitive decline and poor quality of life, factors which are already compromised in normal weight patients with schizophrenia. Here we outline the current strategies against antipsychotic-induced weight gain, and we describe peripheral and cerebral effects of the gut hormone glucagon-like peptide-1 (GLP-1). Moreover, we account for similarities in brain changes between schizophrenia and overweight patients. DISCUSSION: Current interventions against antipsychotic-induced weight gain do not facilitate a substantial and lasting weight loss. GLP-1 analogs used in the treatment of type 2 diabetes are associated with significant and sustained weight loss in overweight patients. Potential effects of treating schizophrenia patients with antipsychotic-induced weight gain with GLP-1 analogs are discussed. CONCLUSIONS: We propose that adjunctive treatment with GLP-1 analogs may constitute a new avenue to treat and prevent metabolic and cerebral deficiencies in schizophrenia patients with antipsychotic-induced weight gain. Clinical research to support this idea is highly warranted.